(untitled) (Global Journal of Human-Social Science, 2024)
The abstract outlines the content of a review on Math Modules, a program designed to facilitate the learning of foundational math skills through cognitive training techniques that are based on theory with a special focus on planning and executive functions, encompassing cognitive flexibility, attentional control, and working memory. The guiding educational principle is drawn from Vygotsky’s concept of zones of proximal development, highlighting the belief that children can accomplish tasks with assistance that they may struggle with independently. In a way, the structure of cognitive training Modules can be viewed as an attempt at construct validity. A review of historical roots of Math modules is presented at some length. The program begins with the division of training the two key components of math proficiency: computing and solving word problems. Both rely on five essential skills.